2017
DOI: 10.1038/srep46146
|View full text |Cite|
|
Sign up to set email alerts
|

Omega-3 Polyunsaturated Fatty Acids Attenuate Fibroblast Activation and Kidney Fibrosis Involving MTORC2 Signaling Suppression

Abstract: Epidemiologic studies showed the correlation between the deficiency of omega-3 polyunsaturated fatty acids (n-3 PUFAs) and the progression of chronic kidney diseases (CKD), however, the role and mechanisms for n-3 PUFAs in protecting against kidney fibrosis remain obscure. In this study, NRK-49F cells, a rat kidney interstitial fibroblast cell line, were stimulated with TGFβ1. A Caenorhabditis elegans fat-1 transgenic mouse model in which n-3 PUFAs are endogenously produced from n-6 PUFAs owing to the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
(50 reference statements)
2
11
0
2
Order By: Relevance
“…Interestingly, the DHA effect was reinforced when combined with short chain fatty acid butyrate [ 84 ]. It is in accordance with a study from Zeng et al, showing that DHA inhibits TGF-β-induced rat renal fibroblast activation at a dose and time-dependent manner [ 85 ]. DHA derivative such as resolvin D1 was also evaluated in extra-intestinal fibrosis model [ 86 ].…”
Section: Beneficial Effects Of Dietary Componentssupporting
confidence: 93%
“…Interestingly, the DHA effect was reinforced when combined with short chain fatty acid butyrate [ 84 ]. It is in accordance with a study from Zeng et al, showing that DHA inhibits TGF-β-induced rat renal fibroblast activation at a dose and time-dependent manner [ 85 ]. DHA derivative such as resolvin D1 was also evaluated in extra-intestinal fibrosis model [ 86 ].…”
Section: Beneficial Effects Of Dietary Componentssupporting
confidence: 93%
“…Zeng, yang et al 2017 [40] cited that omega3 can suppress TGFβ1-induced fibroblast activation at a dose and time dependent manner. Additionally [41] revealed that omega -3 PUFAs down-regulate the expression of profibrogenic genes in activated HSCs(hepatic stellate cells) and fibrotic liver.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LysoPC can promote oxidative stress, inhibit glucose transport and insulin-mediated glucose metabolism, and inhibit the activity of Na + -K + -ATP enzyme, thus causing abnormalities in cell structure and function. The changes of LysoPCs are closely related to the renal fibrosis process and oxidative stress reaction in rats with renal fibrosis (Kang et al, 2015;Zeng et al, 2017;Sun et al, 2018;).…”
Section: Discussionmentioning
confidence: 99%